On the advantages and disadvantages of virtual continuing medical education: A scoping review - Cheng, Courtney; Papadakos, Janet; Umakanthan, Ben; Fazelzad, Rouhi; Martimianakis, Maria Athina (Tina); Ugas, Mohamed; Giuliani, Meredith Elena (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Introduction: With the COVID-19 pandemic, most continuing medical education activities became virtual (VCME). The authors conducted a scoping review to synthesize the advantages and disadvantages of VCME to establish the impact of this approach on inequities that physicians face along the intersections of gender, race, and location of practice.

(untitled)
Introduction : Par suite de la pandémie de la COVID-19, la plupart des activités de formation médicale continue ont été offertes en ligne. Les auteurs ont effectué une revue exploratoire de la littérature visant à faire la synthèse des avantages et des inconvénients de la formation médicale continue en mode virtuel (FMCV) et à évaluer les effets de cette approche sur les inégalités qui affectent les médecins en fonction du sexe, de la race et du lieu d’exercice.